REFLEKSI ETIKA PROFESI AKUNTAN PUBLIK DENGAN KARAKTER PEWAYANGAN : PANCA PANDAWA DAN SRI KRESNA - Putri Prawitasari, Putu; R.Aprilyani Dewi, Putu Pande (Universitas Sarjanawiyata Tamansiswa, 2023)
Wayang is one of the cultural spirits that has taken root in Indonesian society. In achieving the vision and mission of the organization, wayang can be used as an illustration and achieve it. The characteristics of this wayang can be impregnated by the auditor's professional ethics. Every profession has a moral commitment, ethics are poured into specific rules as a guideline for the professional development that is carried out. This commitment is outlined as a form of professional ethics that must be carried out and adhered to. This study uses a qualitative method approach and techniques for collecting/processing data analysis in this study using a literature study on the basic principles of public accounting profession ethics which are reflected through the puppet characters Panca Pandawa and Sri Kresna. Yudistira's character traits are relevant to the basic principles of accountant ethics, namely integrity. Accountants should also have ethical principles like Bima's. By upholding the principle of objectivity, accountants will be free from various conflicts of interest that will interfere with the professionalism of their profession. The third characteristic and quality is reflected by Arjuna, relevant to the basic principles of accountant ethics, namely Professional Competence and Prudence. Sri Kresna can be represent a role model for accountants in maintaining credibility.